TEKNIK ASEPTIK PADA PEMASANGAN INFUS TERHADAP KEJADIAN FLEBITIS: TINJAUAN LITERATUR - Ana Ana; Edison Geovano (Jurnal Kesehatan, 2025)
Background: Phlebitis is one of the most common complications of intravenous catheterisation that can affect patient safety and comfort. One of the main causes of phlebitis is nurses' non-compliance with aseptic technique principles during intravenous catheterisation procedures. The high incidence of phlebitis in various hospitals indicates the need for evaluation of the implementation of aseptic techniques by healthcare workers. Objective: This study aims to identify and synthesise research findings related to the relationship between aseptic techniques in intravenous catheterisation and the incidence of phlebitis in hospitalised patients. Method: This literature review examined ten research articles published between 2017 and 2024, obtained from various institutions and national journals. Inclusion criteria included quantitative studies with observational or experimental designs that examined the relationship between aseptic techniques and phlebitis. Data were extracted and synthesised narratively and presented in tabular form. Results: All ten studies reviewed demonstrated a significant association between aseptic techniques and the incidence of phlebitis, with a p-value < 0.05. Factors such as nurse compliance with six-step hand washing at five moments, use of sterile personal protective equipment (PPE), skin disinfection before puncture, and infusion placement according to SOP were proven effective in reducing the incidence of phlebitis. The study also showed that the location of placement, catheter size, and infusion duration contributed as risk factors. Conclusion: The consistent application of aseptic techniques in accordance with procedures has been proven to reduce the incidence of phlebitis. Continuous education, monitoring, and audits of nurses' compliance with aseptic procedures are highly recommended to improve the quality and safety of nursing care.